Physicians' Knowledge and Practices Regarding Asthma in Jordan: A Cross-Sectional Study - Eman Z. Dahmash (Frontiers Media S.A., 2021)
Objectives: Asthma is a chronic non-communicable disease that causes significant morbidity and mortality and requires ongoing clinical care. Appropriate knowledge by physicians is vital in the management of asthma. Therefore, this study aims to explore and identify the gaps in physicians' knowledge and practices concerning the management of asthma.Methods: A cross-sectional study using an online survey was conducted in Jordan to understand the gap in knowledge and practices in the management of asthma among physicians. A previously validated questionnaire was employed, the Physicians' Practice Assessment Questionnaire (PPAQ). The knowledge questions based on the Global Initiative for Asthma (GINA) guidelines were used to assess knowledge and practice among the study's participants. Predictors of good practice were identified using logistic regression.Results: A total of 271 physicians participated in this survey. The overall knowledge among physicians scored above 78%. However, gaps were pertinent to identifying the signs of asthma attacks that accounted for 61.9% of the participants, whereas only 67.6% of the physicians knew the drugs used for the management of asthma. The study revealed alarming results when practices were assessed, with the overall percentage of physicians applying the required practices did not exceed 57.1 ± 25.7%. Logistic regression analysis to determine predictors of good practice showed that out of several independent variables, physicians who see 6-10 asthma patients per day are five times more likely to follow the guidelines' recommendations in their practice; senior physicians (>50 years old) and those who see 1-5 asthma patients daily are around two times more likely to follow the guidelines (p 0.001).Conclusions: The findings of this study identified the need to transform knowledge into practice. This could be achieved through professional education and constant reminders to physicians in a simple form, as well as a clinical audit of practice. There is a need for novel knowledge transfer approaches to induce behavioral and practice change toward the management of asthma.